The Importance of Virtual Enterprise Systems in Times of Crisis - Ahmad Shatat; Abdallah Shatat (International Journal of Supply Chain Management, 2021)
Virtual enterprise systems are noticeably expanding, which shortly will reveal a substantial impact on the traditional organizational model. The illustration of the major challenges and the Critical Success Factors (CSFs) of the virtual enterprise systems implementation will help other organizations to adopt the virtual enterprise systems efficiently and take advantage of this novel virtual cloud computing revolution especially in times of crises such as Covid-19. This research identifies the top ten CSFs that contribute in delivering a successful virtual enterprise systems implementation. A survey instrument was distributed to 50 enterprises that currently using virtual enterprise systems. The research outcomes indicate positive and significant relationship between eight CSFs and the virtual enterprise systems implementation. However, only two factors demonstrate positive and insignificant correlation. Overall, the results of this study show a notable impact of the CSFs on the virtual enterprise systems implementation.